2008
DOI: 10.1089/acm.2007.0665
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deep-Tissue Massage Therapy on Blood Pressure and Heart Rate

Abstract: Additional scientific research in this area is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 16 publications
5
28
3
2
Order By: Relevance
“…Kaye et al (22)showed that there was a signi icant reduction of mean HR of 10.8bpm, however, both the method of measuring the HR and the massage technique were different from the present study, thereby limiting comparison of the behavior of this variable between the two studies.…”
Section: Resultscontrasting
confidence: 72%
“…Kaye et al (22)showed that there was a signi icant reduction of mean HR of 10.8bpm, however, both the method of measuring the HR and the massage technique were different from the present study, thereby limiting comparison of the behavior of this variable between the two studies.…”
Section: Resultscontrasting
confidence: 72%
“…Previous studies have shown that when moderate to deep pressure is employed a single MT treatment elicits a parasympathetic nervous system response characterized by decreased HR 36 and reduced systolic BP 37 Such changes in autonomic nervous system activity may have an impact on brachial artery FMD responses to MT. Our studies showed no significant changes in HR (EMI and MT: 73.1 ± 0.7; EMI only: 74.6 ± 1.7; and MT only: 68.6 ± 1.0, p > 0.05) or systolic BP (EMI and MT: 117.1 ± 0.7; EMI only: 116.7 ± 1.2; and MT only: 118.5 ± 0.8, p > 0.05) among the groups from baseline to 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Previous studies have evaluated the effectiveness of aromatic therapies by measuring blood pressure, heart beat, respiratory rate, and blood oxygen levels. 8,20,[22][23][24] In aromatherapy, essential oils derived from plants are added to a base massage oil or unscented lotion. The essential oils are claimed to exhibit a wide range of medicinal properties and to affect wound healing, infection, and blood circulation.…”
Section: Introductionmentioning
confidence: 99%